Application Of Value Stream Mapping (VSM) In Manufacturing Industry (Case Study : Jati Beringin Sdn. Bhd.) - Meor Mohd Azwan , Sahran (UTeM, 2010)
In manufacturing system, waste does not add value to the final product or company. Cost will be pay for this waste. Value Stream Mapping (VSM) will provide detailed understanding of all the processes involved in production and thus will improve it. A metal manufacturing industry will involve in this project, which is Jati Beringin Sdn. Bhd. the current problem that was being faced by JBSB is low production rate in ABC suspension hook product due to the high demand of the product. This project research is conducted to analyze the current flow of manufacturing / production system. The data had been collected to implement the tools for maximizing the productivity performance through time study and interview. From the data used in VSM, it shows the overall performance of the production line which is easy to see the overview of the production flow activities. Implementations of VSM tools are carrying out in waste analysis of manufacturing flow and improve the productivity by eliminate the waste. This project will focus on the ABC suspension hook product. The significant factor that influence the high lead time is the process flow facility and changeover time which reducing the productivity through the handling time and setup time. From the implementation of SMED and re layout the assemble process the time was being reduced.